On the Implications of Immigration Policy Restricting Citizenship: Evidence from the Dominican Republic - Catalina Amuedo-Dorantes; Carlos Gratereaux Hernández; Susan Pozo (Institute of Labor Economics (IZA), 2017)
In 2010, an amendment to the Dominican constitution weakened the concept of jus soli citizenship by denying Dominican nationality to individuals born on Dominican soil to irregular immigrants. A few years later, in 2013, the Dominican High Court denationalized large numbers of individuals by reinterpreting language in the prior constitution to, in effect, apply the newer citizenship requirements retroactively to 1929. We gauge the impacts of changes to Dominican citizenship laws on Haitian immigrants and their descendants, to whom, many believe, these policies were directed. We find that the constitutional amendment affected informal employment of some Haitians and their descendants. Furthermore, the High Court's ruling resulted in a significant reduction in the share of Haitian-descendant youth registered in school. Non-attendance was attributed primarily to lack of appropriate documents. Given the rise of nationalist sentiments and discussions to further restrict and revoking citizenship in various regions of the world today, it is important to further explore how these policies ultimately impact targeted and vulnerable populations.
Keywords: F22; F63; F66; F68; J61; K37; 330; immigration policy; birthright citizenship; Dominican Republic; Haiti